The relationship between accommodation, food quality, and customer relations towards tourist satisfaction in Malaysia - Mohamad Alliff Che Rahim; Mohamad Israfel Mokhtar; Mohamad Nor Afiq Mohd Nor Khalid; Mohamad Shafiq Ikhwan Maidi (2023)
Tourist satisfaction measurement has become an important issue in the tourism industry because this industry necessitates a high level of interaction between contact personnel (frontline employees) and tourist, and because quality perceptions are primarily based on the performance of subjective (intangible) criteria. Thus, the amount of satisfaction with services provided by tourists may have a direct towards on the level of satisfaction with services provided by tourists. The purpose of this study is to assess the relationship between accommodation, food quality, customer relations and tourist satisfaction. The debate is based on the findings of a study of Malaysian tourists. The purpose of this research is to examine the relationship of accommodation, food quality, and customer relations between tourist satisfaction among local tourist in Malaysia. It is discovered accommodation, food quality, and customer relations were that affected tourist satisfaction among local tourist in Tourism Industry Malaysia. The local tourist around the Peninsular of Malaysia were targeted respondents and a total of 256 respondents were successfully responded through the online survey. Data collected was analysed by using Statistical Package for Social Science (SPSS) version 29.0. SPSS Statistical addresses the entire statistical analysis process such as planning, data collection, analysis, reporting for better decision making and performance. Pearson correlation coefficient was used in this research to investigate the relationship between accommodation, food quality, and customer relations toward tourist satisfaction. The result shows a significance effect of accommodation, food quality, and customer relations toward tourist satisfaction. Through this study can understand the accommodation, food quality, and customer relations that affect tourist satisfaction among local tourist in Malaysia. Keywords: Tourist Satisfaction, Tourism Industry, and Local Tourist